Pesantren dan Pembaharuan - Ruswanto, Ruswanto (Universitas Islam Negeri Raden Intan Lampung, 2016)
Boarding School is the oldest Islamic institution in Indonesia which has a very important role in the spread and consolidation of public adherence to Islam. But since when actually boarding school began to stand, is not known for certain, but researchers have found that in the 16th century boarding school institutions has grown. Among the researchers are also differences of opinion about the origins of the term and the Pondok Pesantren, some argue comes from within and in part argues from the outside. The cottage-boarding school originally taught about fiqh, tafsir, tasawwuf and the classics as a feature of Pesantren traditional, then with the rise of reformism as the influence of scientific and technological advances, the boarding school was also affected reformism, and this is a positive development the boarding school itself. But although affected reformism boarding school, boarding school never taught radicalism / extremism, because schools are actually contrary to Islamic teachings and ways of proselytizing Islam.